Active sway control of a gantry crane system using delayed feedback signal controller - Wan Mohd Saifuddin, W Zamani (2010)
Gantry Cranes are common industrial structures that are used in building construction, factories, and harbors. These cranes are usually operated manually. With the size of these cranes becoming larger and the motion expected to be faster, the process of controlling them became difficult without using automatic control methods. In general, the movement of cranes has no prescribed path. Cranes have to be run under different operating conditions, which makes closed-loop control preferable. The aim of this project is to develop a controller to reduce the sway angle of the rope for a two dimensional gantry crane system. The 2D-gantry crane system consists of a cart, rope, payload, actuator as well as controller. In this project, the control technique to be implemented to control the sway angle of the rope is Delayed Feedback Signal (DFS). In DFS, the control signal is calculated based on delayed position feedback. The performance on system in 2D-gantry crane focused on the sway angle of the hoisting rope and its corresponding Power Spectral Density (PSD) on the sway angle response. Finally, the comparative assessment of the effects of the system using DFS controller is tested by using different values of the parameters such as mass of the load, length of the rode and the initial point of release load.